Effect of Concentration of Electrolyte in Polymer Coatings Through Post-Polymerization of Acrylamide - Ji Shukla, Ram; Kumar Sinha, Anil (Asian Journal of Chemistry, 2010)
We present here a preliminary report on effect of change in concentration of electrolyte on coating-weight of polymer during post-polymerization.